2000
DOI: 10.1212/wnl.54.1.240
|View full text |Cite
|
Sign up to set email alerts
|

Serum cholesterol, APOE genotype, and the risk of Alzheimer’s disease: A population-based study of African Americans

Abstract: A significant interaction among total serum cholesterol (TC), APOE genotype, and AD risk was found in a population-based study of elderly African Americans. Increasing TC was associated with increased AD risk in the group with no epsilon4 alleles, whereas TC was not associated with increased AD risk in the group with one or more epsilon4 alleles. Further study of the relationship between cholesterol and APOE genotype is needed to confirm this association, but the results suggest that cholesterol may be a poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
121
1
4

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(130 citation statements)
references
References 9 publications
4
121
1
4
Order By: Relevance
“…76 Thus RAGE plays a direct and indirect role in AD pathogenesis, in particular, the apparent inverse relationship between sRAGE and cholesterol may add yet another modulatory effect on Ab metabolism as cholesterol is a known mediator of inflammation and APP processing. [93][94][95][96][97][98][99][100][101][102][103][104] Efflux of Ab: LRP-1/Ab interactions at BBB LRP-1 is a multi-ligand lipoprotein receptor involved in the mediation of endocytosis or activation of signalling molecules for a diverse range of secreted and membrane-bound ligands. Receptor activating protein (RAP) is a 39 kDa chaperone protein that binds to LRP-1 and regulates its tertiary structure.…”
Section: Influx Of Ab Rage/ab Interactions At Bbbmentioning
confidence: 99%
“…76 Thus RAGE plays a direct and indirect role in AD pathogenesis, in particular, the apparent inverse relationship between sRAGE and cholesterol may add yet another modulatory effect on Ab metabolism as cholesterol is a known mediator of inflammation and APP processing. [93][94][95][96][97][98][99][100][101][102][103][104] Efflux of Ab: LRP-1/Ab interactions at BBB LRP-1 is a multi-ligand lipoprotein receptor involved in the mediation of endocytosis or activation of signalling molecules for a diverse range of secreted and membrane-bound ligands. Receptor activating protein (RAP) is a 39 kDa chaperone protein that binds to LRP-1 and regulates its tertiary structure.…”
Section: Influx Of Ab Rage/ab Interactions At Bbbmentioning
confidence: 99%
“…9 Many risk factors are well-characterized, including age and family history, 10 -14 whereas many others are under investigation, including education level, 15,16 head trauma, 17,18 high blood pressure, 19 caloric intake, and high cholesterol. 20,21 Regarding genetic factors, rare mutations on genes coding for amyloid precursor protein, presenilin 1, and presenilin 2 have been identified that are deterministic for early-onset AD. 22 Apolipoprotein E (APOE), in contrast, affects susceptibility to AD and has three major forms.…”
mentioning
confidence: 99%
“…BACE cleaves APP and releases a large N-terminal fragment (sAPPβ). The membrane-anchored frag- [73,75] Decreased [65] β-amyloid (Aβ) Decreased [45,46] No difference [79][80][81][82] No difference [47] Aβ1- 40 No difference [24] No difference [83] Increased [84] Decreased [85] Aβ1- 42 Decreased [24] Increased [83] -Aβ1-42/Aβ1-40 ratio Decreased [48] No difference [83] Decreased [78,84,86] APP ratio --Decreased [90][91][92][93] Ubiquitin Increased [24] No difference [148] BACE1 Increased [67] --Cholesterol -Decreased [94,95] Increased [96][97][98] 24S-hydroxycholesterol Increased [102] No difference [103] Decreased [104] Homocysteine -Increased [106,107,109] Epidermal growth factor -Decreased [111] Decreased [93] Increased [112] Glial cell line-derived growth factor -Decreased [111] No difference …”
Section: Aβ1-42mentioning
confidence: 99%